Optimization in strength-ductility of Mg-RE-Zn alloy based on different repetitive upsetting extrusion deformation paths - Guoqin Wu; Zhaocan Li; Jianmin Yu; Yunfang Liu; Zhimin Zhang; Beibei Dong; Huagui Huang (Materials & Design, 2023)
This study investigated the effects of different repetitive upsetting extrusion (RUE) deformation paths on the microstructures and mechanical properties of Mg-9.32Gd-3.72Y-1.68Zn-0.72Zr (wt%) alloy. Bimodal microstructures were observed in all RUE deformed samples. Increasing the RUE ratio under the same cumulative strain enhanced the dynamic recrystallization (DRX) process, resulting in higher aspect ratios of deformed grains and dynamic precipitation of β phases. The bulk long period stacking ordered (LPSO) phases promoted the DRX process through a particle-stimulated nucleation mechanism, while the β phases hindered the growth of DRXed grains by a pinning effect during deformation. As the RUE ratios increased, the LPSO phase gradually aligned towards the extrusion direction. The R1P3 sample demonstrated the best balance between strength and ductility under small RUE ratio and multi-pass deformation, with ultimate tensile strength, tensile yield strength (TYS), and elongation reaching 382.5 ± 3.1 MPa, 302.3 ± 4.2 MPa, and 8.7 ± 0.5%, respectively. The different contributions of LPSO phases strengthening and heterogeneous deformation-induced (HDI) strengthening led to variations in TYS in different samples. Adjusting the uniformity of the deformed grain size in the bimodal microstructure based on HDI strengthening can further enhance the synergistic improvement of the alloy's strength and ductility.